Courage as Mediator between Positive Resources and General/Domain-Specific Well-Being Indices - Ernesto Lodi; Lucrezia Perrella; Rita Zarbo; Patrizia Patrizi (MDPI AG, 2022)
Background: the current post-pandemic situation has exacerbated the effects already present due to the recent socio-economic crises belonging to the first two decades of this century: perception of instability, fears, concern for the future, underemployment, undignified work. This situation has negatively impacted life in general, career paths, and perceived quality of life, especially for new generations. Positive resources such as optimism and hope can have a positive effect in countering these effects which are impacting student academic satisfaction, life satisfaction, and flourishing. In the hypothesis, courage acts as a mediator for both domain-specific and general well-being, as perceived by college students. Methods: the research involved 410 Italian university students. Five rating scales were used: Visions About the Future, Courage Measure, Satisfaction with Life Scale (SWLS), the Flourishing Scale, and College Satisfaction Scale. Results: All research variables were significantly and positively correlated. The mediation model almost totally confirmed the hypotheses, as the relationship between optimism and academic satisfaction was totally mediated by courage. In other cases, optimism and hope had both a direct and an indirect effect, mediated by courage, on the life satisfaction, academic satisfaction, and flourishing of college students. Conclusions: the findings are discussed with recent theories and research on this topic, and suggestions are provided with practical implications for those involved in supporting the choice and construction of career paths.